Construction Brick Production Industry in Southern Thailand: a Case Study of Kiln - Phawat Prommuang; Somchai Seviset; Songwut Egwutvongsa (Revista de Gestão Social e Ambiental, 2024)
Purpose: To study the kiln that affect the construction brick production industry and to provide guidelines for solving problems. Method: This is qualitative research collecting data from 17 Kiln brick production industry Owners with in-depth interview. Data is analyzed by content and thematic analysis. Results and Conclusion: (1) Physical characteristics of the furnace square brick kiln model. The structure of this kiln is made of cooked bricks into a rectangular permanent wall. There is a firewood compartment and a brick entry door on the side. Production capacity is 50,000-100,000 bricks/stove. Specific energy was 1.6-3.8 MJ/kg of brick, some stoves use 7.8 MJ/kg brick. (2) Burning temperature. Brick firing in Thailand usually ends at 900 degrees Celsius, with brick heating, brick drying, brick kilning, and temperature reduction. which uses a fairly high temperature for burning. (3) The burning time is approximately 7 days, which corresponds to the temperature of the firing side by heating the bricks, baking the bricks, burning the bricks, and reducing the temperature. By using firewood as a leaven. Therefore, there is a lack of technology development in brick production and efficient brick firing with a long firing period. (4) Heat energy loss. Brick firing in Thailand usually ends at a temperature of 900 degrees Celsius and is then turned off for a few days. To reduce cracking due to sudden temperature changes, then turn on the kiln to let the bricks cool naturally allowing the bricks to cool naturally. The heat energy stored is left and that is a loss of heat energy. Research Implications: Brick burning uses a lot of energy, firewood as fuel, and the efficiency of the kilns used is quite low. It is likely that the efficiency of brick kilns will be improved or brick kilns with high thermal efficiency to be used as a replacement to achieve high efficiency. This allows the brick production industry to continue to exist. Originality/Value: The improvement of fuel using for Kiln in brick burning can be improved for more effectiveness and clean environment.
Keywords: Recycling and utilization of industrial and municipal waste in materials production; Building materials and conservation; Concrete and Cement Materials Research